2008
DOI: 10.1038/sj.ki.5002618
|View full text |Cite
|
Sign up to set email alerts
|

Rio de La Plata study: A multicenter, cross-sectional study on cardiovascular risk factors and heart failure prevalence in peritoneal dialysis patients in Argentina and Uruguay

Abstract: A multicenter cross-sectional study was performed to evaluate the prevalence of heart failure (HF) and the associated cardiovascular (CV) risk factors in 298 peritoneal dialysis (PD) patients from Argentina and Uruguay, representing almost 30% of the total number of PD patients in the two countries. Bidimensional echocardiography, electrocardiography, and biochemical analysis were performed. Systolic HF was defined as an ejection fraction <50%. According to echocardiography, 84.6% showed left ventricular hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
2
6
0
Order By: Relevance
“…Brazil is a country of continental dimensions, with large ethnic, geographic, and cultural diversity, and with substantial social and regional inequalities (3,10). Brazilian PD patients have social characteristics similar to the ones described in other studies performed in Latin America that point to a low ES in this population group (7,17,25). These factors make the results of this study fairly representative, at least for the Latin American countries.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Brazil is a country of continental dimensions, with large ethnic, geographic, and cultural diversity, and with substantial social and regional inequalities (3,10). Brazilian PD patients have social characteristics similar to the ones described in other studies performed in Latin America that point to a low ES in this population group (7,17,25). These factors make the results of this study fairly representative, at least for the Latin American countries.…”
Section: Discussionsupporting
confidence: 59%
“…These factors make the results of this study fairly representative, at least for the Latin American countries. Indeed, Moretta et al (25) have recently reported the results of a multicenter cross-sectional study performed in a population representing almost 30% of the PD patients in Argentina and Uruguay. Regarding socioeconomic status, 44% of all patients were under the poverty line, and 25% of all patients were required to start on PD because there was no other RRT option available (25).…”
Section: Discussionmentioning
confidence: 99%
“…Moretta et al. reported that anemia was significantly associated with LVH in PD patients (12). Further, Toprak et al.…”
Section: Discussionmentioning
confidence: 95%
“…In a recent study from Latin America on 298 prevalent PD patients, systolic heart failure was strongly associated with diabetes and hypoalbuminaemia [28], factors we found to be strong predictors of mortality. In addition, anaemia was associated significantly with left ventricular hypertrophy.…”
Section: Discussionmentioning
confidence: 67%